ChemInform Abstract: Base‐Controlled Selectivity in the Synthesis of Linear and Angular Fused Quinazolinones by a Palladium‐Catalyzed Carbonylation/Nucleophilic Aromatic Substitution Sequence. Issue 3 (January 2015) - Chen, Jianbin; Natte, Kishore; Spannenberg, Anke; Neumann, Helfried; Langer, Peter; Beller, Matthias; Wu, Xiao‐Feng
Abstract The Pd‐catalyzed carbonylative coupling of ortho‐fluoro substituted bromobenzenes with 2‐aminopyridines is reported.